Flowthrough Omental Flap for Vascularized Lymph Node Transplant of the Lower Extremity. Issue 3 (March 2022) - Lee, Broderick S.; Granoff, Melisa D.; Pardo, Jaime; Sun, Wei; Critchlow, Jonathan F.; Tsai, Leo; Upton, Joseph; Singhal, Dhruv
Abstract : Summary: Vascularized lymph node transplantation is a surgical approach for the treatment of chronic lymphedema. However, there is no clinical standard for flap placement nor vascular anastomoses. The authors propose a novel flowthrough configuration for an omental vascularized lymph node transplant in the popliteal space. To prepare the popliteal space for an omental free flap, the medial popliteal fat pad and medial head of the gastrocnemius muscle were debulked. Venous anastomoses were completed with vein couplers, joining the right gastroepiploic vein to the medial sural venae comitantes and the left gastroepiploic vein to the lesser saphenous vein. Arterial anastomoses were hand sewn, joining the right gastroepiploic artery to the proximal medial sural artery and the left gastroepiploic artery to the distal medial sural artery, to create the flowthrough configuration. A retrospective review of patients who underwent this procedure at a single institution was performed. Six patients with chronic lymphedema of the lower extremity underwent vascularized lymph node transplantation from June of 2019 to November of 2020. Five patients underwent at least 3 months of postoperative surveillance, with no postoperative complications reported. In this technique contribution, the authors describe a novel flowthrough configuration for an omental free flap to the popliteal space. The popliteal space offers an aesthetically favorable recipient location when appropriately prepared. The medial sural vessels are ideal recipient vessels for the flowthrough omental flap. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.